Custom-made 3D printed masks for children using non-invasive ventilation: a comparison of 3D scanning technologies and specifications for future clinical service use, guided by patient and professional experience. (18th August 2021) - Willox, Matt; Metherall, Peter; McCarthy, Avril D.; Jeays-Ward, Katherine; Barker, Nicki; Reed, Heath; Elphick, Heather E.
Abstract: Non-invasive ventilation (NIV) is assisted mechanical ventilation delivered via a facemask for people with chronic conditions that affect breathing. Mass-produced masks are available for both the adult and paediatric markets but masks that fit well are difficult to find for children who are small or have asymmetrical facial features. A good fit between the mask and the patient's face to minimise unintentional air leakage is essential to deliver the treatment effectively. We present an innovative use of 3D assessment and manufacturing technologies to deliver novel custom-made facemasks for children for whom a well-fitting standard mask is not available. This paper aims to describe the processes undertaken to investigate and compare currently available technologies for 3D scanning children and to explore the design of a system for creating custom-made paediatric NIV masks within the NHS. The paper therefore considers not only the quality and accuracy of the data, but also other factors such as the time and ease of process. Searches for all currently available scanning technologies were made. Photogrammetry image stitch using a smartphone and a digital camera, and two structured light scanners were selected and compared in the laboratory, in discussion with user groups, and in adult volunteers. Using the processes described, it became apparent that the optimal 3D scanning system for this purpose was the handheld structured light scanner. This option offered both superior accuracy and convenience and was more cost effective.